Hate crime recording and data collection practice across the EU (Justice / FRA, European Union Agency for Fundamental Rights, 2018)
Across the European Union, people face hatred because of their skin colour, ethnicity, religion, gender or sexuality. In response, the EU and its Member States have introduced laws against hate crime and support services for victims. But these will only fulfil their potential if victims report hate-motivated harassment and violence to the police, and if police officers record such incidents as hate crimes. This report provides rich and detailed information on hate crime recording and data collection systems across the EU, including any systemic cooperation with civil society. In so doing, it can support efforts to strengthen recording and data collection as well as capacity-building activities to counter hate crime – essential elements of effectively combating prejudice, supporting victims and fostering inclusive societies.